FAKTOR EKSPLOITASI DAN KUANTIFIKASI LIMBAH KAYU DALAM RANGKA PENINGKATAN EFISIENSI PEMANENAN HUTAN ALAM - Juang Rata Matangaran (Bumi Lestari Journal of Environment, 2013)
AbstractThe objectives of the research were to find out the exploitation factor and quantify oflogging residue from forest harvesting operation. Logging residue is defined as stump,trimming from stem, trimming from upper stem and branches which has 30 cm as minimumdiameter and 4 meter of minimum length. Data was collected from two forest company, inCentral Kalimantan and West Sumatera. Data were measured at 10 sample plots in each 1hectare at those both location. Result of the study showed that logging residue occurred atthe harvested site, landing site and at the logyard. Logging residue in each hectare atCentral Kalimantan more than West Sumatera but in each tree quantity of logging residuewas nearly same at both location.The percentage of logging residue at Central Kalimantanwas 33,8%, and at the West Sumatera was 30,4 %. Exploitation factor of logging operationwas 0,75 at West Sumatera and 0,74 at Central Kalimantan. This number indicated that therecovery rate of forest harvesting operation was about 75 % at those both forest companies.